The Role of Parents in Shaping Children's Character in Interacting with the Opposite Gender (A Case Study in Metro City) - Khuzaifah, Cicih Nur; Syarafuddin, Muhsan (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
The determining factor for a child's development both physically and mentally is none other than the role of parents. Parents themselves are the most important figures in directing and forming children's character, through various kinds of parenting patterns. Character education in children is very important in shaping character, personality, ethics and positive values which are instilled in a child through the image of their parents. And as a human being we definitely need interaction and our own interaction lasts throughout our life, so this can be said to be social interaction, especially in interacting and mingling with our environment. Parents also need to remember and pay attention, that the way to explain boundaries and rules in interacting with the opposite sex does not involve strict prohibitions. The aim of this research is to find out how the role of parents in a metro city shapes the character of their children and how they maintain boundaries, norms and etiquette when interacting with other people or the opposite sex. This research uses a qualitative approach to analyze this study. Apart from that, interviews, observation, and documentation are other data collection techniques used in this research. The conclusion from this research is the important role of parents in the process of forming children's character. Likewise, in terms of interactions with other people or the opposite sex, parents must be able to provide insight and guidance regarding boundaries, rules and etiquette in interactions.